Effect of boiling on the texture of cassava clones: a comparison of compressive strength, intercellular adhesion and physiochemical composition of the tuberous roots - Eggleston, G.; Asiedu, Robert (1994)
A highly significant relationship was found between the compressive strength of eight boiled cassava (Manihot esculenta Crantz) tuberous roots and their intercellular adhesion, as measured by a retained dry weight method, suggesting that compressive strength is a measure of cell separation. In general, compressive strength is related to amylopectin content, intercellular adhesion strength and moisture levels. The addition of calcium ions to the boiling water progressively increased compressive strength, with a concomitant reduction in dry weight loss and water absorption, until a saturation point was reached. For seven improved clones, moisture level was inversely related to compressive strength. One local Nigerian cassava variety, Isunikankiyan, demonstrated markedly different physicochemical characteristics to the improved clones: it had the lowest compressive strength with a relatively low moisture level, and its endogenous calcium content was ten times higher and less tenaciously held. It is suggested that other compositional and/or structural differences are involved in determining the final texture of boiled Isunikankiyan. These findings indicate that cooking (boiling) behaviour of cassava depends on several rather than one single parameter and may be regarded as the result of several complex processes.